Proces tworzenia budżetów projektów - Wieczorek, Dariusz (A Process of Project Budgeting, 2006)
Features of a project involve the use of special management instruments allowing to monitoring of a project during its execution. A process of budgeting is one of the most important aspects in project planning. The budget, if it is prepared properly, presents costs estimated separately for each single task, specified in work breakdown structure. Moreover, it is necessary to take into consideration a schedule of project execution, presented in a Gantt chart. It allows to prepare a budget of a project from the dynamic point of view. The dynamic budget structure gives a universal instrument, bringing useful information in all stages of project management process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 415-424